TINGKAT MOTIVASI DALAM MENGIKUTI EKSTRAKURIKULER BELA DIRI KARATE (Studi Survei Peserta Didik di SMP Negeri 2 Kembayan) - Sirapika Sirapika; Victor G Simanjuntak; Andika Triansyah (Universitas Tanjungpura, 2021)
AbstractThe problem in this study is about the ups and downs of students' motivation in participating in Karate extracurricular activities at SMP N 2 Kembayan. The purpose of this study is to determine the level of student motivation in participating in Karate extracurricular at SMP N 2 Kembayan. The research method used in this research is descriptive quantitative. The sample used the saturated sample technique, that is all 20 students of SMP N 2 Kembayan who took Karate extracurricular activities. The data collection technique used in the study is questionnaire, which is measured using a Likert scale. Data analysis was carried out to find the percentage by dividing the actual score by the ideal score multiplied by 100%. The results of the reliability test calculation show that the Cronbach alpha value > r count (0,656 > 0.632). The results of the research, and data analysis showed that the average of the results of the intrinsic factor was 36.6%, while the result of the extrinsic factor was 63.4%. Thus, it can be concluded that the most dominant factor in students' motivation towards karate extracurricular is external factors with 63.4%.Keywords: Motivation, Extracurricular, beladiri